Environmental factors associated with biological use and surgery in inflammatory bowel disease. Issue 4 (23rd September 2020) - van der Sloot, Kimberley W J; Geertsema, Paul; Rijkmans, Hanneke C; Voskuil, Michiel D; van Dullemen, Hendrik M; Visschedijk, Marijn C; Festen, Eleonora A M; Weersma, Rinse K; Alizadeh, Behrooz Z; Dijkstra, Gerard
Abstract: Background and Aim: While major efforts were made studying the complex etiology of inflammatory bowel disease (IBD) including environmental factors, less is known about underlying causes leading to the heterogeneous and highly variable course of disease. As cigarette smoking cessation is the best‐known environmental factor with beneficial effect in Crohn's disease (CD), more exposome factors are likely involved. Further insights into the role of the exposome in heterogeneity of disease might not only further knowledge of underlying pathways, but also allow for better risk stratification. Methods: Seven hundred twenty‐eight IBD patients completed the validated Groningen IBD Environmental Questionnaire, collecting exposome data for 93 exposome factors. Associations with disease course, that is, for need for surgery or biological therapy, were evaluated using univariate and multivariate‐adjusted logistic regression modeling. Results: No significant associations were seen after Bonferroni correction. However, 11 novel exposome factors were identified with P  < 0.05. Two factors were associated with course of CD and ulcerative colitis (UC): beer (CD OR0.3/UC OR0.3) and cannabis (0.5/2.2). While in CD, carpet flooring (0.5) was associated with biological use, and four factors were associated with surgery: working shifts (1.8), appendectomy (2.4), frequent tooth brushing (2.8), and large household size (0.1). For UC, migrants more often required biologicals (10.2). Childhood underweight (3.4), amphetamine use (6.2), and cocaine use (4.8) were associated with surgery. Five factors were replicated. Conclusions: We identified 16 environmental factors nominally associated with biological use and surgery in established IBD. These new insights form an important stepping stone to guide research on biological pathways involved, risk stratification, tailor‐made interventions, and preventive strategies in IBD.